Pengaruh Pengembangan Sumber Daya Manusia dan Kemampuan Kerja terhadap Peningkatan Kualitas Produksi di TV Sumsel : PT. TIVI Indonesia Inter Medianet Group) Palembang - Siti Shara Aliyah; Muhammad Wadud; Meilin Veronica (Jurnal Bisnis, Manajemen, dan Ekonomi, 2022)
This study aims to analyze the effects of human resource development and work ability on improving the quality of production on TV Sumsel Palembang. Samples were selected using the saturated sample technique. Data of 60 respondents were collected through a questionnaire and analyzed employing the multiple linear regression method. The results of the investigation exhibit that partially each human resource development and work ability has a significant effect on increasing the quality of production. These empirical findings can provide benefits for TV Sumsel Palembang. The leader of the company should optimize human resource development and employee work abilities factors to improve production quality